ISLAMIC BANKING IN LIBYA – ITS REALITY AND THE CHALLENGES IT ENCOUNTERS - Khaled Hassan Abdulnabi Ahmed; Murni Bint Yusuf; Shahir Akram Hassan (International Journal of Accounting, Finance and Business, 2024)
The reality of Islamic banking in Libya is tainted with some distress and ambiguity due to the late joining of the Arab and Islamic countries in the Islamic banking system. The country’s entry into a state of political, administrative and financial instability in recent years due to the change in the political situation in 2011. This study aimed to shed light on the reality of Islamic banking in Libya and the challenges it faces to become among its counterparts from Arab and Islamic countries in the field of Islamic banking, as well as proposing effective solutions to eliminate the most important obstacles to the process of Islamic banking in Libya. This proposing will be through briefly reviewing of Islamic banks, their origin and development, and mentioning their importance, functions, concept, objectives, characteristics and types. The review also addressed the relationship Islamic banking with the Central Bank, and finally addressed the banking sector in Libya. The librarian and historical approach were utilized in this study. The results revealed that the performance of Islamic banks in Libya is weak and the process of development within this sector is slow as well.